2008
DOI: 10.1097/cad.0b013e32830f902b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying N 1, N 11-diethylnorspermine-induced apoptosis in a human breast cancer cell line

Abstract: Polyamine analogue treatment results in growth inhibition and sometimes in cell death. Therefore, polyamine analogues are considered in the treatment of cancer; however, the cellular properties that govern sensitivity are not known. The objective of this study was to elucidate molecular mechanisms behind apoptosis induced by the polyamine analogue N, N-diethylnorspermine (DENSPM). Four different breast cancer cell lines were treated with DENSPM. Cell death was evaluated with flow cytometry and a caspase 3 assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This effect is similar to that of ANTMHspd [16] but not that of DENspm [24], for DENspm only triggered the release of cytochrome c from mitochondria without decreasing the MMP of mitochondria. Previous studies have shown that Bcl-2 family proteins were usually involved in polyamine conjugate induced mitochondria apoptotic signal pathway [25,26]. Accordingly, we turned our attention to Bad and Bcl-2, two pivotal pro-apoptotic and anti-apoptotic Bcl-2 family members [27].…”
Section: Discussionmentioning
confidence: 99%
“…This effect is similar to that of ANTMHspd [16] but not that of DENspm [24], for DENspm only triggered the release of cytochrome c from mitochondria without decreasing the MMP of mitochondria. Previous studies have shown that Bcl-2 family proteins were usually involved in polyamine conjugate induced mitochondria apoptotic signal pathway [25,26]. Accordingly, we turned our attention to Bad and Bcl-2, two pivotal pro-apoptotic and anti-apoptotic Bcl-2 family members [27].…”
Section: Discussionmentioning
confidence: 99%
“…The L56Br-C1, MCF-7, SK-BR-3, and HCC1937 cells were cultured as described by Holst et al [33]. JIMT-1 cells were cultured in DMEM/Ham’s F12 medium supplemented with 10% fetal calf serum, non-essential amino acids (1 mM), insulin (10 μg/ml), penicillin (100 U/ml), and streptomycin (100 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Balabhadrapathruni et al [ 68 ] showed that a combination of BE-3-3-3 and the pure antiestrogen, ICI 182780 caused down-regulation of the anti-apoptotic Bcl-2 and Bcl-XL proteins and increased the level of the pro-apoptotic Bax protein in MCF-7 and T-47D breast cancer cells. The efficacy of polyamine analogues on breast cancer cells might be governed in part by their effects on the expression of proapoptotic and antiapoptotic proteins in these cells [ 69 ]. In the case of ERα-positive tumors, the involvement of genomic and non-genomic pathways has also to be considered in mechanistic studies [ 70 ].…”
Section: Polyamine Analogues and Breast Cancer Therapeuticsmentioning
confidence: 99%